Short sleep duration is associated with specific food intake increase among school-aged children in China: a national cross-sectional study - Muqing Cao; Yanna Zhu; Fan Sun; Jingyin Luo; Jin Jing (BMC, 2019)
Abstract Background The relationship between sleep duration and food intake is unclear. This study aims to examine the relationship among children aged 6-17 years in China. Methods The sample consisted of 70,519 children aged 6-17 years, which were randomly selected from 7 representative areas from China, from September to November, 2013. In the structured questionnaire, children reported daily sleep hours (less than 7 h, 7-9 h and more than 9 h), weekly food intake amount (including vegetables, fruit, sugar beverages and meat), physical activity and sedentary time. The relationship of sleep duration with vegetable, sugar beverage, fruit and meat intake was evaluated by multi-nominal logistic regression and multi-variable adjusted. Results A total of 62,517 children (51.6% boys) completed the study. Short sleep duration (SSD, < 7 h) was independently associated with increased sugar beverage intake (SBI, Odd Ratio, OR: 1.29, 95% CI: 1.19-1.40) but decreased vegetable (VI, OR: 0.94, 95% CI: 0.90-0.98) & fruit intake (FI, OR: 0.94, 95% CI: 0.88-0.99). Stratified by age and gender, SSD increased SBI for boys of both young (6-12 years) & older (13-17 years) groups and older girls (ORs: 1.25, 1.25, 1.49, 95% CI: 1.08-1.44, 1.04-1.50, 1.22-1.81, respectively), but decreased VI and FI for older girls (ORs: 0.84& 0.81, 95% CI: 0.74-0.96& 0.68-0.96, respectively). Conclusions Among school-aged children in China, short sleep duration was associated with increased risks of more sugar beverage intake among those younger and boys but less vegetable & fruit intake among those older and girls. Longitudinal research is needed to clarify the causation in between.